2012
DOI: 10.1371/journal.pone.0032056
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Respiratory Virus-Associated Pneumonia in Urban Poor Young Children of Dhaka, Bangladesh, 2009–2011

Abstract: BackgroundPneumonia is the leading cause of childhood death in Bangladesh. We conducted a longitudinal study to estimate the incidence of virus-associated pneumonia in children aged <2 years in a low-income urban community in Dhaka, Bangladesh.MethodsWe followed a cohort of children for two years. We collected nasal washes when children presented with respiratory symptoms. Study physicians diagnosed children with cough and age-specific tachypnea and positive lung findings as pneumonia case-patients. We tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
71
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 34 publications
10
71
3
Order By: Relevance
“…Our study is similar in scope and design to that of Homaira et al in Dhaka, Bangladesh 8 , which reported a lower overall rate of ARI (1.25/child-year) and a higher rate of LRTI (52/100 child years), but these differences are partly due to differences in study design. We defined ARI by parental report of symptoms while in the Dhaka study, children observed to have symptoms at the time of a household visit were referred to the clinic, and only children presenting to the clinic could be diagnosed with ARI.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Our study is similar in scope and design to that of Homaira et al in Dhaka, Bangladesh 8 , which reported a lower overall rate of ARI (1.25/child-year) and a higher rate of LRTI (52/100 child years), but these differences are partly due to differences in study design. We defined ARI by parental report of symptoms while in the Dhaka study, children observed to have symptoms at the time of a household visit were referred to the clinic, and only children presenting to the clinic could be diagnosed with ARI.…”
Section: Discussionsupporting
confidence: 70%
“…5-9,11-13 Recent household-based studies of viral ARI among children in developing countries report rates ranging from 1.2 to 2.4 ARI/child-year, with pneumonia rates of 12 to 50 per 100 child-years. 6,8,9 Several studies have examined the contribution of respiratory viruses to ARI in developing nations, 13-16 but most are health center-based, relying on passive surveillance and lacking clearly-defined population denominators for calculating incidence rates. There is a particular lack of data regarding incidence and etiology of ARI in rural, high-altitude, low population-density areas, despite higher morbidity and mortality of ARI in such areas.…”
Section: Introductionmentioning
confidence: 99%
“…We conducted this study from July to September of 2011 in the Mirpur area of urban Dhaka among mothers with at least one child 5 years old recruited from an ongoing observational study unrelated to hand hygiene. 20 The study area was selected for the handwashing trial, because this area represents the other low-income urban slums of Bangladesh with high levels of environmental contamination. Selection of hands and first scrubbing time.…”
Section: Methodsmentioning
confidence: 99%
“…This ward of low-income Bangladeshis and displaced ethnic Biharis has 20,576 persons/km 2 (i.e., 0.4 miles 2 ), 39% of which are aged less than 17 years; a mean literacy of 59% among females (76% of whom are homemakers); and a median monthly household expenditure (a proxy for income) of US$290 among >90% of the households. Women in our study were previously enrolled during pregnancy in a community-based influenza birth cohort study that explored potential associations between severe respiratory illness and cognitive development by identifying influenza illness, assessing household factors, and quantifying the development of children from birth to 2 years of age (Homaira et al, 2012).…”
Section: Study Populationmentioning
confidence: 99%